2008
DOI: 10.1007/s11270-008-9867-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence the Transport of Bacillus cereus Spores through Sand

Abstract: The goal of this study is to clarify the surface-chemical and microphysical variables that influence bacterial spore transport through soil, thereby defining the factors that may affect spore transport velocity. Bacillus cereus spores were continuously monitored in a soil column under saturated conditions with experimental variations in soil grain size (0.359 and 0.718 mm), pH (7.2 and 8.5), and water flow rate (1.3 and 3.0 mL/min). Increasing soil grain size, flow rate, and pH resulted in enhanced spore movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A sandy gravel layer of 2-3 m can be found between soil and groundwater. Pore size exclusion phenomena rather than hydrophobic interactions between spores and soil organic content seem to play an important role in the filtration process in soils [ 65 , 68 ]. However, an earlier study investigating infiltration processes in the same experimental site suggested that preferential flows observed during high rain events had a quantitative effect on this alluvial aquifer recharge in only isolated cases but could induce local short-term contamination of the groundwater [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sandy gravel layer of 2-3 m can be found between soil and groundwater. Pore size exclusion phenomena rather than hydrophobic interactions between spores and soil organic content seem to play an important role in the filtration process in soils [ 65 , 68 ]. However, an earlier study investigating infiltration processes in the same experimental site suggested that preferential flows observed during high rain events had a quantitative effect on this alluvial aquifer recharge in only isolated cases but could induce local short-term contamination of the groundwater [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To cope with it, two different size of soil columns were used, one column of 9.7 cm in length and 3.1 cm in diameter for the saturated hydraulic conductivity experiment and the other column of 20.0 cm in length and 9.0 cm in diameter for the tracer and nutrient leaching experiment [13] (Figure 1(a) and Figure 1(b)). The soils used in these experiments consisted of Jumunjin standard sand (Jumunjin, South Korea) with a particle size of 0.718 ± 0.123 mm.…”
Section: Experimental Procedure: Soil Column Experimentsmentioning
confidence: 99%
“…There has been limited research into the significance of organic carbon components of the soil solution or of the properties of cell surfaces in microbial transport through the vadose zone after an application of organic wastes. Increases in pH were correlated with enhanced attachment of Bacillus spores to silt [ Kim et al , 2009] but decreased the adhesion of Pseudomonas putida to clay minerals or goethite [ Jiang et al , 2007]. Theoretically, electrostatic adhesion of bacterial cells to charged soil minerals depends on the pH of the suspending solution and the isoelectric points of the two interacting surfaces [ Rong et al , 2010].…”
Section: Introductionmentioning
confidence: 99%